SCIENTIFIC EXERCISES APPROACH TO SCOLIOSIS (SEAS) METHODOLOGY IN ADOLESCENT IDIOPATHIC SCOLIOSIS - Stamenka Mitova (Peytchinski Publishing, 2020)
The aim of this study is to investigate the changes in the spine, post-training in corrective exercises with the SEAS method in moderate idiopathic scoliosis. Material and Methods: A contingent in the present study was 42 subjects with mild adolescent idiopathic scoliosis. The methodology of research includes conducting functional studies and tests - an anamnesis (including physical exercise data, motor behavior, etc.), somatoscopy (examination), radiographic and postural assessment, GPS100 system test, and Adams test. Physiotherapy methodology includes training in specific corrective exercises for scoliosis by the SEAS method with a duration of 7 days of 60 minutes. Results: 42 subjects with mild adolescent idiopathic scoliosis were studied, of which 26 girls and 16 boys with a follow-up time of 12 months. Mean values of height and weight are as follows for girls 156.3±7.26cm and 49.23±4.59kg, for boys 158.1±5.27cm and 52.88±4.76kg. The mean Cobb's angle of scoliosis in girls was 20.08°±2.47°, for boys 23.06°±3.66°. Changes in Cobb's angle in girls and boys are reported. The mean Cobb's angle in pre-treatment girls from 20.08°±2.47° to 15.73°±2.05° at the end of the follow-up (p<0.001). In pretreatment boys at 23.06°± 3.66° Cobb, after 12 months of correction exercise the SEAS angle was 17.25°±2.96°, (p<0.001). The most significant influence is in the boys. Conclusions: SEAS is an approach to the treatment of scoliosis, which differs from many others due to continuous improvement and development, to maintain the evidence base through research results.